Assessment of effect of flood mitigation construction at Perkampungan Sungai Isap, kuantan - Ahmad Syahmi Azri, Mohmad Anua (2015)
Throughout the last century flooding has been one of the most costly disasters in terms of both property damage and human casualties. The flooding in 2001/2002 at the basin Sungai Kuantan, the government has built Chereh Dam at upstream of Sungai Kuantan in 2008 and a bund along the Sungai Kuantan at Perkampungan Sungai Isap and surrounding villages. The flood-inducing rains incident in December 2013 at this area, raised concern in effectiveness of those mitigation infrastructures. The main objective of this study was to assess of effect of flood mitigation construction at Perkampungan Sungai Isap, Kuantan. The specific objective were; to analysis rainfall characteristics of study area during the floodinducing rains, and to assess changes of flood prone of study area, pre and post of existing river bund. Rainfall for five months (Oct. Nov, Dec, Jan, Feb) for each year (2000-2001, 2001-2002, 2007-2008 pre-bund year; 2010-2011, 2013-2014 post-bund) data collected from the satellite were tabulated based on daily rainfall. Water balance model was used to calculate the possible retention depth water. The analysed of satellite-based rainfall data were compare to JPS flood report relating to flooding incident.